Effect Of Winding Angle Due To Internal Pressure In Hybrid Polymer-Metal Cylindrical Composite - Khairul Izman , Abdul Rahim (2014)
The hybrid cylindrical composite structure using glass polymer types and metal alloy as the liner subjected to high internal pressure is still under development stage. Glass-fiber with quasi-isotropic lamination overwrap stainless steel is selected to be the main focus in this research. Struktur hibrid polimer-logam berbentuk silinder mengunakan polimer jenis gentian kaca dan logam aloi sebagai pelapik yang dikenakan tekanan dalam tinggi masih dalam peringkat pembangunan. Gentian kaca dengan susunan kuasi-isotropic menyaluti keluli tahan karat adalah fokus utama dalam kajian ini.